Relationship between genetic polymorphisms of RFC1 A80G and nonsymdromic cleft lip with or without palate - Wang, Yun; Song, Xiaoming; Guo, Jinzhen; Zhu, Wenli (Wei sheng yan jiu, 2009)
To explore the relationship between genetic polymorphisms of reduced folate carrier (RFC)1 A80G and nonsymdromic cleft lip with or without palate on Chinese population. There were 97 NSCL/P case-parent triads those were selected as case group. At the same period, 104 healthy subjects were selected together with their biological parents as control group. For all subjects the polymorphisms of RFC1 A80G were examined by PCR-RFLP method. There was no statistical difference in genotype and gene frequencies for RFC1 A80G variants among family members between case group and control group in offsprings and fathers and mothers (P < 0.05). The odds ratio (OR), confidence interval (CI) and P value of offspring, father and mother genotype (AG) were 0.87 (0.44-1.70), 0.657; 1.09 (0.54-2.21), 0.788; 1.63 (0.79-3.36), 0.152 respectively. The OR, CI and P value of offspring, father and mother allele (GG) were 0.48 (0.19-1.23), 0.094; 0.93 (0.38-2.23), 0.850; 1.30 (0.46-3.67), 0.584 respectively. The OR, CI and P value of off